GDS XEROX: ADDRESSING THE RIGHT SEGMENT (IITM Journal of Business Studies, 2024)
Nowadays, several businesses are introducing  new product lines or services, but are not  correctly allocating their efforts to reach their  target segments. Businesses are spending a lot of  money on awareness through different platforms,  but are they reaching the right segment? This case  tackles a prominent issue that many businesses  face today. GDS Xerox is a Xerox concessionaire  company that does the following activities:  selling printing machines and equipment,  offering maintenance services, and has its own  business centers offering printing services. The  company recently introduced a new service in  its business centers, which is selling customized  giveaways (including mugs, coasters, etc.). GDS  Xerox is indecisive about what efforts should it  should allocate to increase sales revenue in the  business services activity after introducing new  services. The company is unsure which segment  it is targeting with these new services. This leads  to allocating marketing activities that target  several segments without focusing on a specific  segment to reach. Is it targeting companies or  individuals? This also leads to a minimal increase  in sales revenue, and low awareness as the target  segment has not been decided yet. The idea of  segmentation is crucial because companies have  a certain budget to spend on marketing, and  indecisiveness about the target audience might  prevent the company from reaching its target  audience. Therefore, the company might not be  able to achieve its objectives
Keywords: businesses; GDS Xerox; companies; audience